The impact of expanded access to antiretroviral treatment on engagement in HIV care and viral suppression among pregnant women living with HIV in South Africa - Cornelius Nattey; Mhairi Maskew; Nelly Jinga; Laura Rossouw; Amy Wise; Nicola van Dongen; Thalia Ferreira Brizido; Maanda Mudau; Karl-Günter Technau; Kate Clouse (PLoS ONE, 2026)
Background Timing of engagement in HIV care in relation to pregnancy impacts maternal outcomes and the risk of vertical transmission of HIV. Option B+, a policy that mandates offering all pregnant women living with HIV (PWLH) lifelong antiretroviral therapy (ART) irrespective of their CD4 count, has been adopted across sub-Saharan Africa, including South Africa since 2015. This study aimed to assess the impact of expanded access to ART on engagement in HIV care and viral suppression among pregnant women in South Africa. Methods This observational study used data from pregnant women living with HIV who delivered at Rahima Moosa Mother and Child Hospital in Johannesburg, South Africa from 2013−2017. Linkage to a national HIV laboratory cohort (the NHLS National HIV cohort) was used to ascertain engagement in HIV care prior to antenatal care (ANC) entry and viral load outcomes. Analyses were stratified by the pre-Option B+ (2013−2014), Option B+ (2015−31 Aug 2016) and Universal Test and Treat (post-01 Sept 2016) eras. We compared engagement rates before and during the Option B+ era and assessed factors associated with HIV care engagement and viral suppression. Risk ratios were estimated using log-binomial regression. Results Among 4,865 PWLH, 65% had evidence of prior engagement in HIV care. Prior engagement in care was higher during the Option B+ (64%) and UTT (71%) eras compared to the pre-Option B+ era (55%). Younger women (18–24 years) were less likely to engage in HIV care than those aged 25–34 years (aRR 0.8, 95% CI: 0.6–0.9). Women with CD4 counts <200 cells/mm³ were less likely to have been engaged in care prior to pregnancy compared to those with CD4 ≥ 500 (aRR 0.6, 95% CI: 0.6–0.7). Primigravid women had a 30% lower likelihood of earlier HIV care engagement compared to those with 2–3 pregnancies (aRR 0.7, 95% CI: 0.5–0.8). Overall viral suppression was higher in women reporting ART use prior to pregnancy compared to those with no prior HIV care (33% vs. 19%, p < 0.001). During the four-year study period, the proportion of PWLH who had a viral load recorded but were not virally suppressed ranged from 22–36%. Conclusion We observed increased engagement in HIV care prior to pregnancy after implementation of policies that expanded access to ART. However, high prevalence of unsuppressed viral load across all policy eras highlights the need for continued monitoring and support to sustain the benefits of this policy. Pregnancy and antenatal care services remain an essential portal of entry to HIV care among PWLH in South Africa. Interventions to improve early ANC attendance and maternal engagement in HIV care prior to pregnancy are critical to eliminate vertical HIV transmission.